Synthesis, Characterization and Screening of Novel 5,6-Dihydroacridine Derivatives as Potent Antidiabetic and Antioxidant Agent (Journal of Basic and Applied Research in Biomedicine, 2016)
Acridine is an important nucleus in heterocyclic compounds which posses a wide spectrum of pharmacological activities. In this present work 10-Chloro-5,6-dihydro-12-phenylpyrimido[4,5-a]acridin-2-amine derivatives (PD-1 to PD-5) and 2-Amino-10-chloro-1,4,5,6-tetrahydro-12-phenylbenzo-[1,7] phenanthroline derivatives (PD-6 to PD-10) were synthesized from (E)-2-Benzylidene-7-chloro-3,4-dihydro-9-phenylacridin-1(2H)-one with guanidine carbonate and malononitrile. All the synthesized compounds have been characterized by using elemental analysis, FT-IR, 1H NMR, 13C NMR spectroscopy and further supported by mass spectroscopy. Purity of all the compounds has been checked on thin layer chromatographic plate and HPLC technique. All the synthesized compounds were tested for in vitro anti-diabetic and anti-oxidant activities. These compounds can be further exploited to get the potent lead compounds. The detailed synthesis and the anti-diabetic and anti-oxidant screening of the new compounds are reported.